2008
DOI: 10.1016/j.clinph.2007.09.140
|View full text |Cite
|
Sign up to set email alerts
|

EEG of chronic marijuana users during abstinence: Relationship to years of marijuana use, cerebral blood flow and thyroid function

Abstract: Objective-Marijuana abuse is associated with neurological changes including increases in frontal EEG alpha during abstinence. Research is needed to assess to what extent these EEG patterns are indicative of cerebral perfusion deficits.Methods-We recorded the resting eyes closed EEG of 75 abstinent marijuana users and 33 control subjects. Fifty-six marijuana users used marijuana for less than eight years and 19 used for eight years or more. The EEG evaluation occurred within 72 hours of admission to an inpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 58 publications
4
24
0
1
Order By: Relevance
“…A recent research had showed an association between duration of marijuana use and reduction in alpha and beta power at posterior electrode locations. 48 Due to marijuana being the illicit drug most referred to the subjects in our sample; it is difficult to rule out its effects on EEG findings, mainly in alpha power band.…”
Section: Discussionmentioning
confidence: 98%
“…A recent research had showed an association between duration of marijuana use and reduction in alpha and beta power at posterior electrode locations. 48 Due to marijuana being the illicit drug most referred to the subjects in our sample; it is difficult to rule out its effects on EEG findings, mainly in alpha power band.…”
Section: Discussionmentioning
confidence: 98%
“…This study described subtle lower levels of T 4 in cannabis abusers compared to control subjects; but all of these values were within the standard range [ 3 ] . TSH was not signifi cantly diff erent between the 2 groups [ 3 ] . A study that was intended to relate thyroid function tests to serum THC levels in humans, which would provide more insights in the interplay of THC and thyroid hormones, could not be found in the literature.…”
Section: Introductionmentioning
confidence: 92%
“…Data about the eff ect of cannabis on thyroid function in humans are very rare. To the best of my knowledge, there is only one study published on this subject [ 3 ] . This study described subtle lower levels of T 4 in cannabis abusers compared to control subjects; but all of these values were within the standard range [ 3 ] .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Clear differences were reported between crack cocaine-dependent subjects who began using as adolescents and subjects who began using as adults. EEG effects of chronic marijuana users during abstinence are reported to be associated with reduced power in alpha and beta bands at posterior sites (Herning, Better, & Cadet, 2008). Chronic marijuana users were earlier found to have an increase in frontal EEG alpha power (Struve et al, 1994).…”
Section: Eeg and Erp In Sudmentioning
confidence: 98%